Challenges Experienced at Age 100: Findings From the Fordham Centenarian Study. Issue 3 (2nd July 2016) - Jopp, Daniela S.; Boerner, Kathrin; Cimarolli, Verena; Hicks, Stephanie; Mirpuri, Sheena; Paggi, Michelle; Cavanagh, Andrew; Kennedy, Erin
ABSTRACT: This article examines the challenges experienced by very old individuals and their consequences for well-being and mental health. In order to capture unique issues experienced in very old age, 75 participants of the population-based Fordham Centenarian Study answered open-ended questions on everyday challenges. Theme-based coding was then used to categorize and quantify responses. The challenges mentioned most often were challenges faced in the functional (e.g., physical health/activities of daily living restrictions, mobility, sensory impairment), psychological (e.g., loss of well-liked activity, dependency, negative emotions, death), and social (e.g., family loss) life domains. Functional challenges were negatively associated with aging satisfaction and positively associated with loneliness. Psychological challenges were positively linked to aging satisfaction. Social challenges were marginally related to loneliness. Notably, challenges were not related to depression. In conclusion, the challenges experienced in very old age are multidimensional and multifaceted, unique in nature, and have differential relations to mental health. Functional, psychological, and social challenges affect very old individuals' lives and therefore need to be better understood and addressed. Given their consequences, it is imperative for policy makers to develop an awareness for the different types of challenges faced by centenarians, as there may be unique policy implications related to each.